Online Physics Learning with Seesaw App Based on Discovery Learning - Silvia Shinta; Dwi Sulisworo (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to analyze the importance of the Learning Management System (LMS) in terms of usefulness, ease of use, ease of learning, and satisfaction. The method used in this study is the use of the Seesaw LMS and discovery learning approach, which was incorporated with constructivist learning theories. The results show that the average for each aspect was 3.11 (usefulness), 3.10 (ease of use), 3.30 (ease of learning), and 3.11 (satisfaction), with a maximum scale of 4. The overall average for all categories was 3.16, indicating that the application is suitable for online learning. The study found that using the features of Seesaw in conjunction with discovery learning can improve the quality of education and increase students' learning outcomes. Implementing Seesaw in the learning process using discovery learning is an appropriate method for online learning. Using Seesaw features and collaborating with other supporting applications like PhET can make the learning process more engaging and not monotonous.